Safety and efficacy of COVID-19 prime-boost vaccinations: Homologous BBIBP-CorV versus heterologous BNT162b2 boosters in BBIBP-CorV-primed individuals. Issue 12 (17th March 2023) - Mallah, Saad I.; Alawadhi, Abdulla; Jawad, Jaleela; Wasif, Pearl; Alsaffar, Basma; Alalawi, Ejlal; Mohamed, Afaf Merza; Butler, Alexandra E.; Alalawi, Batool; Qayed, Donia; Almahari, Sayed Ali; Mubarak, Ali; et al.
Highlights: There is increasing concern regarding waning immunity against SARS-CoV-2, breakthrough infections and immune-evasive variants. Heterologous prime-boost strategies are gaining attention due to theoretical superiority of immune stimulation, supply shortage and adverse event concerns with certain vaccine platforms. More robust humoral response was observed in the heterologous BNT-boosted group compared to the homologous BBIBP primed and boosted group. Significantly greater levels of spike (S) protein specific antibodies were observed in the heterologous group compared to the homologous one. The heterologous BNT-boosted group had a higher rate of non-serious adverse events, all of which were self-limiting, indicating it to be a safe and well-tolerated approach. Abstract: Background: Booster vaccine doses against SARS-CoV-2 have been advocated to address evidence of waning immunity, breakthrough infection, and the emergence of immune-evasive variants. A heterologous prime-boost vaccine strategy may offer advantages over a homologous approach, but the safety and efficacy of this approach with the mRNA vaccine BNT162b2 (BNT: Pfizer) and inactivated BBIBP-CorV (BBIBT: Sinopharm) vaccines have not been studied. Methods: We conducted a non-randomized, non-blinded phase II observational community trial across Bahrain, investigating the reactogenic and immunogenic response of participants who had previously received two doses of BBIBP, followed by a third booster dose of either BBIBP (homologous booster) or BNT (heterologous booster). Immunogenicity through serological status was determined at baseline and on the following 8th week. Reactogenicity data (safety and adverse events) were collected throughout study period, in addition to participant-led electronic journaling. Results: 305 participants (152 BBIBP and 153 BNT booster) were enrolled in the study, with 246 (127 BBIBP and 119 BNT booster) included in the final analysis. There was a significant increase in anti-SARS-CoV-2 antibody levels post booster administration in both groups; however, the heterologous BNT arm demonstrated a significantly larger mean increase in the level of spike (S) antigen-specific antibodies (32.7-fold increase versus 2.6, p < 0.0001) and sVNT neutralising antibodies (3.4-fold increase versus 1.8, p < 0.0001), whereas the homologous arm demonstrated a significant increase in the levels of nucleocapsid (N) antigen-specific antibodies (3.8-fold increase versus none). Non-serious adverse events (injection site pain, fever, and fatigue) were more commonly reported in the heterologous arm, but no serious adverse events occurred. Conclusion: Heterologous prime-boost vaccination with the mRNA BNT162b2 (Pfizer) vaccine in those who had received two doses of inactivated virus BBIBP-CorV (Sinopharm) vaccine demonstrated a more robust immune response against SARS-CoV-2 than the homologous BBIBP booster and appears safe and well tolerated. Clinical Trial Registry Number (ClinicalTrials.gov): NCT04993560.